SHRIMP U-Pb zircon geochronology of the Dhzida intrusive rocks in the Tavt ore field, northern Mongolia - Oyungerel, Sodnom; Lee, Insung; Jargal, Luvsanchultem; Tegshbayar, Batsuren; Maibayar, Otgonsuren (Geological Issues, 2023)
The Tavt ore field is located in the northern part of Mongolia. The ore field containing the Tavt gold deposit, which covers 90 square km, is in the Dzhida terrane at the junction of two regional faults that trend NW and NE, respectively. This terrane, which spans the border between Mongolia and Russia is overlapped and stitched with Orkhon-Selenge trough assemblages. The geology of the deposit consists of the Early Paleozoic Dzhida intrusive complex, the Middle Paleozoic Tes intrusive complex, the Late Paleozoic Selenge intrusive complex, the Early Mesozoic Orkhon complex, and the Ediacaran-Early Cambrian metavolcanic Badariingol formation, Early Cambrian silicic-terrigenous-carbonate Burgelt formation. Zircons SHRIMP U–Pb ages from the Tavt intrusive rocks are slightly different: 505.3+3.8 Ma for plagiogranites, 512.7+4.1 to 514.4+3.0 Ma for granodiorites, 506+3.4 Ma for quartzmonzodiorites, 510.1+2.9 Ma for monzodiorites and 509.8+3.7 Ma for subalkaline diorites, respectively. It indicates that the Dzhida intrusions have formed at the island arc environment since the middle Cambrian ages.